Reading the Campus Through Translation: A Critical Study of Indonesian–English Public Signs in Higher Education - Widarwati, Nunun Tri; Gama, Betty; Purnomo, Budi; Arianti, Arin; Giyatmi, Giyatmi (Langkawi: Journal of The Association for Arabic and English, 2025)
The strategic establishment of an internationalized status has led many Indonesian universities to implement bilingual policies on campus public signage. However, a significant research gap exists regarding a systematic analysis of the translation quality in this domain, despite its crucial role in projecting the institution's global image. This study aims to investigate the phenomenon of Indonesian-English translation in the public signage at a state university in Surakarta. Employing qualitative research grounded in critical content analysis, data were collected through photographic documentation of 32 public signs. The analysis was framed within the theoretical lens of translation techniques and methods to assess the correspondence between source and target texts. The findings reveal the use of four translation methods: word-for-word, literal, adaptation, and free translation, with the literal method being the most predominant. In terms of translation techniques, adaptation was the most frequently employed, alongside linguistic compression, literal translation, and established equivalence. This indicates a concurrent tendency to retain source-language structures while modifying cultural elements, occasionally leading to inconsistency. The implication is that the university must employ a more considered approach, potentially involving linguistic experts, to ensure the signage achieves clarity, accuracy, and cultural appropriateness for an international audience